"An invisible map" - maternal perceptions of hunger, satiation and 'enough' in the context of baby led and traditional complementary feeding practices. (1st May 2020) - McNally, Janet; Hugh-Jones, Siobhan; Hetherington, Marion M.
Abstract: Mothers' responsiveness to hunger and fullness cues has been implicated in the development of infant overweight, and baby led weaning (BLW) is argued to be one way to protect against overfeeding. Whilst studies have examined maternal perceptions of hunger, fullness and adequate intake to some degree in traditional weaning (TW) contexts, less is known about this in BLW. This study therefore aimed to understand and compare maternal perceptions of cues and intake in BLW and TW. Eleven mothers of infants (7–24m) participated in semi-structured interviews based on discussions of short videos featuring participants feeding their infants. Interviews were read and transcribed in full. Data were selected for coding which addressed mothers' perceptions of infant hunger, fullness and sufficient consumption and subsequently subjected to template analysis. A sample of data was coded to produce an initial template which was applied to all interviews and revised in an iterative process to produce a final template for interpreting findings. Mothers in the study were adept at recognising fullness cues and gauging feeding state. Both groups perceived similar hunger cues although TW mothers reported a wider range of fullness cues. Both groups used numerous strategies for judging the adequacy of their babies' intake. These included the use of infant cues, however perceived adequacy of intake was also influenced by factors such as infant tiredness and maternal worries about over and under-eating. Findings have implications for the development of responsive feeding interventions while also highlighting the utility of video elicited interviews for understanding feeding interactions.